2020
DOI: 10.1242/jeb.222703
|View full text |Cite
|
Sign up to set email alerts
|

The energetic costs of living in the surf and impacts on zonation of shells occupied by hermit crabs

Abstract: Crashing waves create a hydrodynamic gradient in which the most challenging effects occur at the wave breaking zone and decrease towards the upper protected tide pools. Hydrodynamic forces depend on the shape of the submerged body; streamlined shapes decrease drag forces compared with bluff or globose bodies. Unlike other animals, hermit crabs can choose their shell shape to cope with the effects of water flow. Hermit crabs occupy larger and heavier shells (conical shape) in wave-exposed sites than those used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Determining what, if any, components of diet contribute to the accrual and retention of red coloration in this species will require experiments with controlled feeding regimens. Future experiments can also separately consider crabs’ ages, which need not be equivalent to their body sizes, given that hermit crabs metabolically control their growth (e.g., Alcaraz and García-Cabello 2017 ; Alcaraz et al. 2020 ), growing only when they acquire larger shells.…”
Section: Discussionmentioning
confidence: 99%
“…Determining what, if any, components of diet contribute to the accrual and retention of red coloration in this species will require experiments with controlled feeding regimens. Future experiments can also separately consider crabs’ ages, which need not be equivalent to their body sizes, given that hermit crabs metabolically control their growth (e.g., Alcaraz and García-Cabello 2017 ; Alcaraz et al. 2020 ), growing only when they acquire larger shells.…”
Section: Discussionmentioning
confidence: 99%
“…We captured 80 Calcinus californiensis (Bouvier 1898 ) hermit crabs of similar size occupying shells of Nerita scabricosta (Lamarck 1822 ) with no apparent damage or epibionts in Troncones, Guerrero, Mexico. The length of the chela (4–6 mm) was used as a preliminary measure to estimate the body size of the hermit crabs (Alcaraz et al 2020 ). We kept the hermit crabs in an individual glass flask, which was also used as respirometric chamber (0.03 L), in a circulating seawater system at 27°C and 34 practical salinity unit (PSU).…”
Section: Methodsmentioning
confidence: 99%
“…This increases the shell’s weight and modifies its centre of mass, making walking uncomfortable for the crab and most probably costly energetically; consequently, the hermit crabs ‘voluntarily’ swap to the alternative refuge provided, even when this is not ideal (e.g. too small or large; Arce & Alcaraz 2013 ; Alcaraz et al 2020 ). However, there are experimental procedures which require the hermit crabs to be ‘naked’ for specific measurements or manipulations prior to starting the trials or after experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…Vance [3] experimentally demonstrated that individuals of P. granosimanus that inhabited smaller shells were at higher risk of crab predation, and Spight [12] postulated that hermit crabs rarely used the species Lirabuccinum dirum's available shells due to its thin walls. Shell weight can also provide hydrodynamic advantages in wave-exposed areas [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Heavier shells display slow growth [5] and references therein, [17]. In hypoxic conditions, some hermit crabs shift to significantly lighter choices [18], and others shift from heavier, conical shells to smaller, lighter, globose ones when moving to areas of slower-flowing water [14]. Female hermit crabs of some species tend to utilize lighter shells than do the males, perhaps due to the additional weight of eggs [19,20].…”
Section: Introductionmentioning
confidence: 99%